Designing of nanoflakes anchored nanotubes-like MnCo2S4/halloysite composites for advanced battery like supercapacitor application. (1st May 2020) - Shinde, S.K.; Ghodake, G.S.; Maile, N.C.; Yadav, H.M.; Jagadale, A.D.; Jalak, M.B.; Kadam, A.A.; Ramesh, Sivalingam; Bathula, C.; Kim, D.-Y.
Abstract: In this study, we report a facile chemical synthesis of a novel MnCo2 S4 /halloysite (HNTs) nanoflakes decorated on nanotubes which coated on Ni foam via a screen-printing technique. The MnCo2 S4 thin films were prepared using a coprecipitation method which demonstrate battery kind of behavior. The MnCo2 S4 /HNTs-based electrode shows a specific capacity of 359 mAh g −1 at 5 mV s −1 with excellent cycling stability. Furthermore, the symmetric system exhibits an outstanding energy density and power density of 6.98 Wh kg −1 and 1976.0 W kg −1, respectively. The results obtained with the MnCo2 S4 /HNTs composite in a symmetric system indicate that this composite material can potentially be used as an alternative electrode material for electrochemical energy storage. Graphical abstract: Image 1 Highlights: Innovative halloysite nanotubes (HNTs) like nanostructures covered on MnCo2 S4 nanoflakes. MnCo2 S4 /HNTs prepared hybrid composite using a simple screen-printing technique. The MnCo2 S4 /HNTs offering excellent specific capacities and cycling stability. Hybrid MnCo2 S4 /HNTs electrode provided higher surface area for supercapacitor.